CENTRAL PRECOCIOUS PUBERTY - Farkhutdinova L. M. (SINAPS LLC, 2017)
The article is devoted to the problem of central precocious puberty - one of the orphan diseases. The modern classification, etiopathogenesis, clinic, diagnosis and differential diagnosis, treatment, prognosis and prevention of the disease are presented. Precocious puberty is much more common in girls than in boys, and the most common pathogenetic option is idiopathic. The pathogenesis is the early activation of the hypothalamic-pituitarysex gland axis, which causes the development of puberty clinically similar to the physiological one. Excess sex hormones lead to the closure of the epiphyses and low final growth. The key diagnostic measure is a test with gonadotropin-releasing hormone, as well as visualizing studies of the brain, adrenals and gonads. The main hormonal criterion for the central form of precocious puberty is a significant increase in luteinizing hormone in response to stimulation with luliberin - more than 10 mU/ml. Gonadotropin-releasing hormone analogues are used for the treatment of central precocious puberty, the continuous injection of which blocks receptors on gonadotropic cells of the pituitary gland, which causes a decrease in the secretion of gonadotropins and, accordingly, sex steroids. Regress of secondary sexual characteristics is observed after 3 months of therapy, decreasein the rate of growth to normal values after 1-1,5 years, decrease in the ratio of bone age to chronological, which improves the growth forecast - by the end of the 3rd year of treatment. Therapy is continued until the onset of puberty, as its cessation causes the resumption of the disease. Treatment is most effective at an early onset, when the bone age does not exceed 12 years. The forecast is favorable in most cases